X-ray and optical spectroscopic study of a γ Cassiopeiae analog source π Aquarii. (14th December 2022) - Tsujimoto, Masahiro; Hayashi, Takayuki; Morihana, Kumiko; Moritani, Yuki
Abstract: γ Cas analog sources are a subset of Be stars that emit intense and hard X-ray emission. Two competing ideas for their X-ray production mechanism are (a) the magnetic activities of the Be star and its disk and (b) the accretion from the Be star to an unidentified compact object. Among such sources, π Aqr plays a pivotal role as it is one of the only two spectroscopic binaries observed for many orbital cycles and one of the three sources with X-ray brightness sufficient for detailed X-ray spectroscopy. Bjorkman et al. (2002, ApJ, 573, 812) estimated the secondary mass >2.0  M ⊙ with optical spectroscopy, which would argue against the compact object being a white dwarf (WD). However, their dynamical mass solution is inconsistent with an evolutionary solution and their radial velocity measurement is inconsistent with later work by Nazé et al. (2019, A&A, 632, A23). We revisit this issue by adding a new data set with the NuSTAR X-ray observatory and the HIDES échelle spectrograph. We found that the radial velocity amplitude is consistent with Nazé et al. (2019, A&A, 632, A23), which is only half of that claimed by Bjorkman et al. (2002, ApJ, 573, 812). Fixing the radial velocity amplitude of the primary, the secondary mass is estimated as <1.4  M ⊙ over an assumed range of the primary mass and the inclination angle. We further constrained the inclination angle and the secondary mass independently by fitting the X-ray spectra with a non-magnetic or magnetic accreting WD model under the assumption that the secondary is indeed a WD. The two results match well. We thus argue that the possibility of the secondary being a WD should not be excluded for π Aqr.